Report of the 15th working committee and general assembly ASEAN Inter-parliamentary organization - Asean inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 1994)
Cuộc họp ủy ban và Hội nghị lần thứ mười năm của tổ chức liên nghị viện ASEAN được tổ chức tại Manila,Philippines từ ngày 19 đến ngày 24 tháng 9 năm 1994.